Report on a new species of Plutomurus (Collembola, Tomoceridae) from a South Korean limestone cave, with notes on its DNA barcode - Chang, Gyudong; Park, Kyung-Hwa (Zootaxa, 2020)
A new species of Plutomurus Yosii, 1956, P. jangamensis sp. nov., was found in a limestone cave of South Korea. The new species is very similar to P. gul (Yosii, 1966) in the general pattern of cephalic and body chaetotaxy, absence of eye, presence of pointed tenent hair, number of lateral macrochaetae in basal segment of dens, and number of mucronal intermediate tooth; however, the two species can be distinguished by the small spines arranged in-a-row along with dental spines and lighter body color. This species, however, shows variability and was not easily classified morphologically as P. jangamensis sp. nov. and P. gul., in terms of body color, formula of dental spine, or even the number of prelabral chaetae. Partial DNA sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene were used as DNA barcodes to distinguish the species. This result suggests that the COI gene is useful for discrimination of P. jangamensis sp. nov. with high support (bootstrap=100). An identification key to the world species of Plutomurus is also provided.